The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1002/chem.201301584
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Theoretical Study of Trifluoromethyl Derivatives of C84(23) Fullerene

Abstract: Trifluoromethylation of a higher fullerene mixture with CF3I was performed in ampoules at 550 °C. HPLC separation followed by crystal growth and X-ray diffraction study resulted in the structure elucidation of nine CF3 derivatives of D2d-C84 (isomer 23). The molecular structures of C84(23)(CF3)4, C84(23)(CF3)8, C84(23)(CF3)10, C84(23)(CF3)12, two isomers of C84(23)(CF3)14, two isomers of C84(23)(CF3)16, and C84(23)(CF3)18 were discussed in terms of their addition patterns and the relative formation energies. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 36 publications
4
45
0
Order By: Relevance
“…Although the carbon cages of C 2v -C 78 (2) and C 2v -C 78 (3) differ by the position of only one C-C bond [2], the addition patterns of the derivatives with equal numbers of CF 3 groups, C 78 (2,3)(CF 3 ) 12 , differ significantly. A similar phenomenon has also been found for (CF 3 ) 12 derivatives of isomers C 84 (22) and C 84 (23), which also differ by the position of one bond on the carbon cages [16,17]. In contrast, the addition patterns of C 78 X 18 (X = Cl, Br) are the same for isomers C 78 (2), C 78 (3), and even C 78 (5) [8][9][10][11] which give rise to co-crystallization phenomena for these halides [8,11] thus demonstrating the levelling effect for a large number of addends on the addition patterns of fullerene derivatives with similar carbon cages.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although the carbon cages of C 2v -C 78 (2) and C 2v -C 78 (3) differ by the position of only one C-C bond [2], the addition patterns of the derivatives with equal numbers of CF 3 groups, C 78 (2,3)(CF 3 ) 12 , differ significantly. A similar phenomenon has also been found for (CF 3 ) 12 derivatives of isomers C 84 (22) and C 84 (23), which also differ by the position of one bond on the carbon cages [16,17]. In contrast, the addition patterns of C 78 X 18 (X = Cl, Br) are the same for isomers C 78 (2), C 78 (3), and even C 78 (5) [8][9][10][11] which give rise to co-crystallization phenomena for these halides [8,11] thus demonstrating the levelling effect for a large number of addends on the addition patterns of fullerene derivatives with similar carbon cages.…”
Section: Discussionsupporting
confidence: 75%
“…Two different starting higher fullerene mixtures were used for trifluoromethylation with gaseous CF 3 I in quartz ampules following a previously described procedure [16][17][18]. The mixture of higher fullerenes C 76 -C 96 (45 mg; MER Corp.) was trifluoromethylated at 560…”
Section: Resultsmentioning
confidence: 99%
“…5 After wards, the use of X ray diffraction method for the deter mination of the cage structures of fullerenes (only for C s C 84 (14) 7 ) or their derivatives confirmed the existence of all the indicated isomers except C 84 (19) and C 84 (24). The presence in the mixtures of C 2v C 84 (18) isomer was confirmed 8 by the crystal and molecular structures of its C 84 (18)(C 2 F 5 ) 12 derivative.…”
mentioning
confidence: 66%
“…17) and C 84 (23)(CF 3 ) 4-18 (see Ref. 18) became available, which in combination with calculations of relative stabili ties allowed one to suggest the schemes of sequential addi tion of pairs of CF 3 groups to the fullerene cage. It was found that trifluoromethylated C 84 (22) and C 84 (23) iso mers have not only similar addition patterns, but also con siderable differences due to the different structures of their carbon cages.…”
mentioning
confidence: 99%
See 1 more Smart Citation